Sanctions, co-sanctions, and counter-sanctions: A multilateral, evolutionary game among three global powers - Peng Zhou; Dong Guo (Cardiff University, Cardiff Business School, 2023)
Facing the sanctions from the West since the annexation of Crimea in 2014, Russia quickly converged to a strong counter-sanction strategy. The US and the EU staggered the strengths of sanctions in turns, with the EU first imposing relatively stronger commercial sanctions first and the US relaying with stronger financial sanctions later. Using US-EU-Russia sanctions as an example, we develop a multilateral, evolutionary game to capture the strategic complementarity between the sanctioners and the sanctionee, as well as the strategic substitutability between the leading sanctioner and the co-sanctioner. In an extended model, the sanction technology is introduced to endogenize how sanctions are designed before deployment. The model is then calibrated to match the summarized stylized facts, to demonstrate the simulated evolutionary paths, and to verify the derived strategic dependence.
Keywords: 330; Sanction; Strategic Dependence; Evolutionary Game Theory